Cardiac DPP-4 inhibition by saxagliptin ameliorates isoproterenol-induced myocardial remodeling and cardiac diastolic dysfunction in rats - Junichi Ikeda; Naoya Kimoto; Tetsuya Kitayama; Shunji Kunori (Elsevier, 2016)
Saxagliptin, a potent and selective DPP-4 inhibitor, is characterized by its slow dissociation from DPP-4 and its long half-life and is expected to have a potent tissue membrane-bound DPP-4-inhibitory effect in various tissues. In the present study, we examined the effects of saxagliptin on in situ cardiac DPP-4 activity. We also examined the effects of saxagliptin on isoproterenol-induced the changes in the early stage such as, myocardial remodeling and cardiac diastolic dysfunction. Male SD rats treated with isoproterenol (1 mg/kg/day via osmotic pump) received vehicle or saxagliptin (17.5 mg/kg via drinking water) for 2 weeks. In situ cardiac DPP-4 activity was measured by a colorimetric assay. Cardiac gene expressions were examined and an echocardiographic analysis was performed. Saxagliptin treatment significantly inhibited in situ cardiac DPP-4 activity and suppressed isoproterenol-induced myocardial remodeling and the expression of related genes without altering the blood glucose levels. Saxagliptin also significantly ameliorated cardiac diastolic dysfunction in isoproterenol-treated rats. In conclusion, the inhibition of DPP-4 activity in cardiac tissue by saxagliptin was associated with suppression of myocardial remodeling and cardiac diastolic dysfunction independently of its glucose-lowering action in isoproterenol-treated rats. Cardiac DPP-4 activity may contribute to myocardial remodeling in the development of heart failure.